(untitled) (Web of Teachers: Inderscience Research, 2024)
Almost all psychologists define adolescence as the most critical age, as a transition between childhood and adulthood. The study of the patterns inherent in this stage of a person’s life makes it possible to trace the transformation of children’s psychological characteristics proper, which occurs within adolescence, as well as to identify the features of the maturing child’s exit beyond childhood and the transition to maturity. The article deals with the concept of intelligence as a mental talent or the ability and dynamics of the intelligence of weak-speech teenagers.